2018
DOI: 10.1111/iji.12379
|View full text |Cite
|
Sign up to set email alerts
|

Allelic and haplotype diversity of HLA‐A, HLA‐B and HLA‐DRB1 gene at high resolution in the Nanning Han population

Abstract: The distribution of human leucocyte antigen (HLA) allele and haplotype varied among different ethnic populations. In this study, we investigated the allele and haplotype frequencies of HLA-A, HLA-B and HLA-DRB1 loci in the Nanning Han population who live in Guangxi province of China. We identified 26 HLA-A, 56 HLA-B and 31 HLA-DRB1 alleles in 562 Nanning individuals of Han ethnic group by sequence-based typing method. Of these, the three most common alleles in HLA-A, HLA-B and HLA-DRB1 loci, respectively, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The frequencies of HLA‐A, HLA‐B, HLA‐C, HLA‐DRB1, and HLA‐DQB1 alleles were various among different populations in the previous reports (Buhler et al, ; Halagan et al, ; Kwok et al, ; Li et al, ; Loubser, Paximadis, & Tiemessen, ; Park et al, ; Pei et al, ; Schmidt et al, ; Wang et al, ; Yang, Chen, Shyr, & Lin, ). According to the previous studies, the distributions of HLA alleles were also difference between the Chinese southern Han population and northern Han population (Deng et al, ; Qin Qin et al, ; Shao et al, ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The frequencies of HLA‐A, HLA‐B, HLA‐C, HLA‐DRB1, and HLA‐DQB1 alleles were various among different populations in the previous reports (Buhler et al, ; Halagan et al, ; Kwok et al, ; Li et al, ; Loubser, Paximadis, & Tiemessen, ; Park et al, ; Pei et al, ; Schmidt et al, ; Wang et al, ; Yang, Chen, Shyr, & Lin, ). According to the previous studies, the distributions of HLA alleles were also difference between the Chinese southern Han population and northern Han population (Deng et al, ; Qin Qin et al, ; Shao et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…Up to now, there were many reports available on the HLA‐A, HLA‐B and HLA‐DRB1 distribution in the Chinese populations (He et al, ; Li et al, ; Pei, Huang, Li, Chen, & Wu, ; Shao et al, ; Wang et al, ), but data on AFs and HFs of HLA‐C and HLA‐DQB1 are limited in Zhejiang Han population. In this study, we firstly reported the distribution of AFs and HFs of HLA‐A, HLA‐B, HLA‐C, HLA‐DRB1, and HLA‐DQB1 loci in Zhejiang Han population at a high‐resolution level.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Because of the nonrandom expression patterns and linkage imbalance of HLA alleles, many studies have determined that the HLA phenotype of any individual has a certain correlation with that person's habitat region, race, disease occurrence, and PRA generation. 4 , 5 , 6 It has also been shown that the long‐term survival rate of a kidney graft increases if the HLA types match to a higher degree. 7 …”
Section: Introductionmentioning
confidence: 99%